Program Fisioterapi Pada Pasien Dengan Kondisi Post-Arthroscopic Partial Meniscectomy Fase 1: Case Report - Afyoga Fahrizal Yahya; Farid Rahman (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Meniscus tear is the second most common knee injury that occurs in athletes with a prevalence of 12% to 14% and an incidence of 61 cases per 100,000 people. Arthroscopic Partial Meniscectomy (APM) is the most common orthopedic surgical procedure for treating meniscus tears worldwide. According to a recent survey, approximately 500,00 Arthroscopic Partial Meniscectomy (APM) is performed annually in the United States. Surgery is considered the gold standard in the management of meniscus tears. The purpose of this study was to determine the effectiveness of the physiotherapy program in the form of Cryotherapy, TENS, NMES, ROM exercise, and Strengthening exercise on the functional improvement of post Arthroscopic Partial Meniscectomy patients. Keywords: Meniscus tear, Arthroscopic Partial Meniscectomy, Cryotherapy, Electrical stimulation, Exercise therapy.